WACANA INTELEKTUAL KEAGAMAAN ISLAM DI INDONESIA DENGAN TIMUR TENGAH - Mohammad Al Farabi (Universitas Islam Negeri Sumatera Utara Medan, 2021)
This article uses a historical historical approach in studying the “religious intellectual traditions in Indonesia” through scientific contacs between Muslim scholars in the archipelago and leading scholars in the Middle East when they studied Islamic sciences, especially in the Haramayn region (Makkah and Madinah). It was through this scientific contact that a generation of Indonesian Muslim scholars or intellectuals was born who colored the growth and development of scientific activity in the archipelago at the end of the 17th century AD until the 20th century AD. In the end, this scientific contact gave birth to a discourse on Islamic intellectual traditions the developed in Indonesia, among others, the transmission of Islamic sciences, the harmonization of sharia and Sufism, the rise of the study of yellow books, the emergence of works of archipelago scholars, the birth of Islamic educational institutions, and the development of neo-sufism and tarekat teachings in Indonesia. Key words: Discourse; tradition; intellectual-religion.